The death of human platelets during incubation in citrated plasma involves shedding of CD42b and aggregation of dead platelets - Hartley, Paul S.; Savill, John; Brown, Simon B. (Thrombosis and Haemostasis, 2006)
The ability to readily identify dead platelets is invaluable to studies examining the means of their death, factors affecting their lifespan and their means of clearance by phagocytes. The aim of the present work was to develop a vital staining procedure for the rapid and objective discrimination of live from dead platelets that accrued in citrated platelet rich plasma (cPRP) incubated at 37°C for several days. By transmission electron microscopy it was noted that platelet death was morphologically similar to necrosis and associated with aggregate formation. The vital dyes calcein-AM and FM 4–64 were found to robustly report the death of platelets and indicated that the aggregates which formed during incubation were populated exclusively by dead platelets. Additionally, platelet death was associated with the shedding of CD42b. Microscopic and cytometric analyses of incubated cPRP indicated that shedding of CD42b and aggregate formation by dead platelets were completely inhibited by the metalloproteinase inhibitor GM6001. Automated counting of platelets incubated in the presence of GM6001 revealed that death did not lead to a loss in cellularity. It is proposed that calcein-AM and FM4–64 are effective as vital stains for the reliable assessment of platelet viability and that platelet aggregation can occur by a novel mechanism dependent upon platelet death and metalloproteinase activity.
Keywords: Platelets; death; metalloproteinase; agglutination; cytometry